In vitro and in silico study of an exclusive insertion in the nicotinamide/nicotinate mononucleotide adenylyltransferase from Leishmania braziliensis. Issue 12 (December 2022) - Ortiz-Joya, Lesly Johanna; Contreras Rodríguez, Luis Ernesto; Ochoa, Rodrigo; Ramírez Hernández, María Helena
Abstract: The intracellular parasite Leishmania braziliensis is the causal agent of cutaneous and mucocutaneous leishmaniasis, a group of endemic diseases in tropical regions, including Latin America. New therapeutic targets are required to inhibit the pathogen without affecting the host. The enzyme nicotinamide/nicotinate mononucleotide adenylyltransferase (NMNAT; EC: 2.7.7.1/18) is a potential target, since it catalyzes the final step in the biosynthesis of nicotinamide adenine dinucleotide (NAD + ), which is an essential metabolite in multiple cellular processes. In this work, we produced and evaluated the catalytic activity of the recombinant protein 6HisΔ241-249 LbNMNAT to study the functional relevance of the exclusive insertion present in the enzyme of L. braziliensis (LbNMNAT), but absent in the primary structure of human NMNATs. Our results indicate that the 241–249 insertion constitutes a structural element that connects the protein structure Rossmann topology with the carboxyl-terminal domain of the enzyme. The removal of this region drastically decreases the solubility, and enzymatic activity of the recombinant, causing its inactivation. Molecular dynamics simulations were carried out with the wild-type and truncated enzymes to verify additional changes in their stability, which indicated a better stability in the wild-type protein. These findings constitute an initial step to identify a new inhibition mechanism for the development of focused pharmacological strategies on exclusive insertions from the LbNMNAT protein. Abstract : Leishmania ; NAD, NMNAT; Deletional mutant; Molecular dynamics.